Tailored methods for mapping urban heat islands in Greater Cairo Region - Esraa Elmarakby; Marwa Khalifa; Abeer Elshater; Samy Afifi (Ain Shams Engineering Journal, 2022)
Globally, there is a rapid development of urban heat island (UHI) detection tools, and their results can be accepted regardless of their accuracy in measuring the real impact of the phenomenon. In this study, we investigated various UHI measuring tools and analysed their findings to better interpret their reliability. The tools in the current research adopted remote sensing and field measurements including those using air temperature monitors and thermal imaging technologies to examine the multiple urban structures of four cases in the Greater Cairo Region. The results showed that UHI detection by remote sensing analysis was affected by normalised difference vegetation index. In contrast, field measurements were also influenced by the albedo of morphological materials present. The conclusions revealed that the tools do not provide the same results and indicate that studying UHIs in the built environment differs from investigating it in a two-dimensional layer using remote sensing.